Urban transport social needs in China: Quantification with central government transit grant. (October 2016) - Deng, Haopeng; Li, Ye; Li, Wenxiang; Yu, Yuewu
Abstract: Social inclusion requires suitable measures to improve public transport, thus satisfying the needs of socially disadvantaged groups (SDGs). Although numerous measures are available in principle, in practice, however, financial problems hinder the implementation of these measures. This study addresses an important issue in China—how to finance a socially inclusive public transport system given the incomplete nature of fiscal reforms at local government level. Central government grants are required to achieve a more equitable distribution of public transport resources. To calculate the demand for central government grants, an approach was developed to quantify transport social needs (TSNs). A primary component regression model was established to identify the factors that affect the SDGs using public transport. Further, a need-based method is proposed for the allocation of central government grants. The allocation procedure was designed with the categorization of cities to avoid distorted incentives, and a two-step formula was used to address the funding allocation equity problems. The data obtained from 252 municipal cities in China in 2010 show that the TSNs were 37.63 billion trip-kilometers. The corresponding central government grant was ¥18.82 billion. The results of the proposed allocation show that more funding was provided to small and low-density cities had unfavorable situations due to local public transport investment. This investigation would help in a more equitable distribution of public transport funding. Highlights: A numeric measurement of transport social needs is developed. The requirement of central government transit grant in China is identified. A need-based allocation procedure of central government transit grant is proposed. Small and low-density cities are most deficient in local transit investment. The proposed allocation results in more equitable distribution of transit funding.